Samuel Richardsons brevromaner - Hultén, Martin (K&K - Kultur og Klasse, 2007)
En litteraturhistorisk placering The Epistolary Novels of Samuel Richardson: Reconsidering the Historical Perspective The epistolary novels of Samuel Richardson were received with enthusiasm throughout Britain and Europe upon their publication in the 1740s and 50s, and they have had their unquestioned place in the literary canon and the literary history of the 18th century, as well as in the many rivalling Rise of the Novel narratives, ever since. The qualities of Richardson’s novels praised by contemporary reading audiences and professional critics were to some extent the qualities we still acknowledge in the the works. And yet I propose to reconsider and modify our ‘historical’ understanding of Richardson’s novels. Richardson scholars from the 1970s onward have deepened our understanding of the contexts of Richardson’s life and writing, and they have shown to what extent both the style, the form, the motifs, and the themes of his novels must be placed alongside the works of rival authors, today much less known, and the comedies and tragedies of the restoration period, just to mention two important fields of inspiration for Richardson. On the basis of their findings we must conclude that the novels we read today when considering Richardson’s works as part of a formal literary history are not quite the same as the novels contemporary readers cherished. There are important differences as well as correspondences between the contemporary reception of Richardson’s works and the reception of professional scholars in the twentieth and twenty-first centuries.